Formulation of The Concept of Designing Swimming Sports Facilities in Mojokerto Regency with A Contextual Approach - Sigmayuriza Devinnandy Trisnanda; Febby Rahmatullah Masruchin; Ibrahim Tohar (Kirana Publisher (KNPub), 2026)
The design of swimming sports facilities requires a strong understanding of local conditions so that the resulting buildings not only meet technical standards, but also align with the needs and identity of the community. Mojokerto Regency, with population growth, increasing interest in sports, and the availability of diverse land between urban and rural areas, presents challenges as well as opportunities in providing adequate swimming facilities. This study seeks to formulate the basic concept of swimming sports facility design through a contextual approach that places geographical, climatic, socio-cultural, regional spatial planning, and swimming pool planning standards in a central position. The research methods include literature review, national–international regulatory analysis, field observation, and identification of community needs and physical environmental characteristics. The results of the research resulted in a basic concept that emphasizes the integration of local contexts, spatial efficiency, environmental sustainability, user comfort, and conformity with FINA standards and national regulations. This concept is expected to be the basis for the process of designing swimming sports facilities that are functional, safe, inclusive, and relevant to the dynamics of the people of Mojokerto Regency, as well as opening up space for the development of more adaptive and sustainable sports facilities.